2014
DOI: 10.3382/ps.2014-03904
|View full text |Cite
|
Sign up to set email alerts
|

Growth, serum biochemistry, complement activity, and liver gene expression responses of Pekin ducklings to graded levels of cultured aflatoxin B1

Abstract: A 14-d study was conducted to evaluate the effects of cultured aflatoxin B1 (AFB1) on performance, serum biochemistry, serum natural antibody and complement activity, and hepatic gene expression parameters in Pekin ducklings. A total of 144 male Pekin ducklings were weighed, tagged, and randomly allotted to 4 dietary treatments containing 4 concentrations of AFB1 (0, 0.11, 0.14, and 0.21 mg/kg) from 0 to 14 d of age (6 cages per diet; 6 ducklings per cage). Compared with the control group, there was a 10.9, 31… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 40 publications
4
31
0
Order By: Relevance
“…Similarly, feed consumption was decreased in AFB1-exposed quail, but body weight and feed conversion were unaffected [126]. In ducks fed AFB1, both feed intake and weight gain were reduced but without affecting feed efficiency [127].…”
Section: Production Lossesmentioning
confidence: 92%
See 2 more Smart Citations
“…Similarly, feed consumption was decreased in AFB1-exposed quail, but body weight and feed conversion were unaffected [126]. In ducks fed AFB1, both feed intake and weight gain were reduced but without affecting feed efficiency [127].…”
Section: Production Lossesmentioning
confidence: 92%
“…This is exemplified by AFB1-reduced total serum protein levels, as the liver is responsible for production of most circulating proteins [88,115,[117][118][119]123,127,129,140,141]. Aflatoxicosis negatively affects albumin, globulin, cholesterol, and triglyceride levels in serum [88,115,117,119,127,129,136,[140][141][142].…”
Section: Hepatotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…For FB 1 , our estimated IC 50 based on 48 and 72 h incubation was 14.27 μg ml –1 (19.8 μ m ) and 4.19 μg ml –1 (5.8 μ m ), respectively, while Creppy et al ( reported that IC 50 values of FB 1 were 45, 31 and 64 μ m in C6 glioma cells, Caco‐2 cells and Vero cells after 48 h incubation. With an IC 50 of 3.69 μg ml –1 (11.8 μ m ) in primary DEF, toxicity potential of AFB 1 was intermediate of the three mycotoxins tested herein, yet in livestock, AFB 1 tend to be the most potent mycotoxin in impairing performance and health (Andretta et al , ; Chen et al , ; Yunus et al , ). This inconsistency might be due to limited activity of hepatic enzymes in the fibroblasts, as AFB 1 needs to undergo an extensive transformation by the hepatic cytochrome P450 family into the metabolically active metabolite, exo‐AFB 1 ‐8, 9‐epoxide, to exert its toxicity (Yunus et al , ).…”
Section: Discussionmentioning
confidence: 87%
“…As secondary metabolites of Aspergillus and Fusarium species, AFB 1 , FB 1 and DON are known to be highly prevalent contaminants in a variety of food and feedstuffs. When consumed by humans or animals, these mycotoxins can cause diverse toxic effects, including growth depression, immunosuppression, liver damage and carcinogenic effects (Chen et al , ; Henry et al , ; Mirocha and Christensen, ; Rotter, ). Similar to our results with testing chemicals, a difference in cell sensitivity has been observed for the three mycotoxins tested.…”
Section: Discussionmentioning
confidence: 99%